FAKTOR PENENTU KINERJA KARYAWAN PADA PT. SEGAR MURNI UTAMA MOJOKERTO - Dau Khusnul Nadhiroh; Mei Retno Adiwati (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
Human resource management (HRM) is a crucial aspect of the company's scope when running its organization in order to realize its vision and mission. Good HRM will result in more productive and efficient HR performance. To achieve maximum performance, it is necessary to minimize work stress within the scope of work and the provision of compensation must also be considered. The purpose of the study was to examine the effect of work stress and compensation on the performance of employees of PT. Fresh Pure Utama Mojokerto. The research sample amounted to 84 respondents with saturated sampling method. Data were collected from respondents' answers through the distribution of questionnaires. Testing the validity and reliability of the questionnaire was carried out first. In testing the hypothesis through the SEM PLS analysis method, it can be seen that the t-test, p-values, and path coefficients show that work stress has a non-significantly negative effect on employee performance, while compensation has a significant positive effect on employee performance. Based on the results of R2, 25% of employee performance is affected by work stress and compensation.